Konsep Pengelolaan Air Limbah Kawasan Industri Makassar (KIMA) - Dewi, Yashinta Kumala; Pratiwi, Nurul; Jinca, Muhammad Yamin (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2020)
Waste problems are one of the trigger factors that can hinder the growth and development of the city of Makassar, which should be able to balance growth and development. The selection of the waste disposal location into the Tallo River due to its location adjacent to the Makassar Industrial area, the waste construction pipeline that has been treated from the installation from the industrial waste treatment is channeled to the Tallo River. The Tallo River pollution condition with an indicator of IP value is equal to 1.38 including under mild pollution status. The purpose of this study is to find out how the ideal management of industrial wastewater is currently in KIMA and to plan the concept of industrial waste management which includes 3 components, namely the distribution, processing and disposal of wastewater networks so as not to have a negative impact on the environment. The analytical method used is analysis of quantity and quality with descriptive methods, comparative analysis and spatial analysis to analyze the location and land needed for KIMA industrial wastewater management. The results of the analysis show that the performance of existing comparative assessments and ideal KIMA limbah water management is at a value of 49.36% C, where the distribution network does not cover all zones, processing only 3 stages and the absence of utilization of treated water. So that the direction of the planning concept needed by KIMA at the initial stage is to complete the distribution network to all service zones by increasing the pipe size to 300 mm and adding 3 stages, procuring the utilization of processed water and the last capacity to 5,000 m3/day with a total area of ​​10,500 m2. Keywords: Zone, Industry, Infrastructure, Sewerage, Makassar